Learning Motivation as A Factor Related to Students' Learning Independence of Class XI at SMK N 1 Kecamatan Luak - Siti Khairun Nisa; Wiwik Gusnita; Juliana Siregar; Cici Andriani (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
The purpose of the study was to describe; (1) the learning motivation of class XI students at SMK Negeri 1, Luak District, (2) the learning independence of class XI students at SMK Negeri 1, Luak District, (3) the relationship between learning motivation and learning independence of class XI students at SMK Negeri 1, Luak District. This type of research is quantitative with a correlational approach. The population of the study was 224 students, with a sample of 143 students of grade XI at SMK Negeri 1, Luak District consisting of 9 classrooms. The research instrument was a questionnaire on student learning motivation and learning independence with a Likert model scale. The data was processed using data description analysis, normality test, linearity, correlation and t-test. The results of the study showed that (1) the learning motivation of class XI students of SMK Negeri 1 Luak District as a whole from 143 respondents was known to have the highest percentage at the "moderate" score of 85 people (59%) so that it can be concluded that the learning motivation of class XI students of SMK Negeri 1 Luak District is in the "moderate" category. (2) the learning independence of class XI students of SMK Negeri 1 Luak District as a whole from 143 respondents was known to have the highest percentage at the "low" score of 42 people (30%) so that it can be concluded that the learning motivation of class XI students of SMK Negeri 1 Luak District is in the "low" category. (3) there is a positive and significant relationship between the learning motivation variable (X) and the learning independence (Y) of class XI students of SMK Negeri 1 Luak District.